The Effect of Price, Brand Image, and Product Quality of Purchase Decision of Xiaomi Smartphones - Ardiansyah, Dimas Bayu Dwi; Aziz, Noor; Fuadiputra, Iqbal Ramadhani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The high number of internet users in Indonesia makes the need for smartphones increasingly increasing. That way the competition to meet the needs of smartphones is very high with competition from various brands. This study aims to determine the effect of price, brand image, and product quality on purchasing decisions. The population in this study were consumers who purchased Xiaomi smartphones in Probolinggo City with a sample of 119 respondents using purposive sampling. This study uses a quantitative method with a descriptive approach and is analyzed using multiple linear regression. The results of this research show that price, brand image, and product quality have a significant positive effect on purchasing decisions. Brand image has the most dominant influence on purchasing decisions.